Territory of Authenticity of Confession in Iranian Islamic Penal Code - مجتبی جعفری (مطالعات فقه و حقوق اسلامی, 2016)
Confession has always been considered in law and jurisprudence.In the Penal Code the legislator has repeatedly spoken about the confession as one of the proofs of evidence. This proof  compared with the other proofs of evidence can be recognized as the best and worst proof. It is the best proof because the judge could decide without any doubt concerning the behavior and responsibility of the accused.  Therefore, in conventional criminal law the confession is known as a king proof. Nevertheless, the confession can be the worst proof because it may be achieved illegitimately and illegally. As it is not unlikely that confessions may be obtained by torture or threat. Naturally, the confession without observing the conditions required by the Common and Divine legislator was not accepted in the criminal process. But, in return, if the confession involves all conditions considered by the legislature, some results will follow which is important in the criminal process. In this article, by reviewing the conditions necessary for the veracity of the confession according to the Penal Code, we have tried to study the effects associated with the correct confession.